Pathological changes in the subsynovial connective tissue increase with self-reported carpal tunnel syndrome symptoms. Issue 4 (May 2015) - Tat, Jimmy; Wilson, Katherine E.; Keir, Peter J.
Abstract Background Fibrosis and thickening of the subysnovial connective tissue are the most common pathological findings in carpal tunnel syndrome. The relationship between subsynovial connective tissue characteristics and self-reported carpal tunnel syndrome symptoms was assessed. Methods Symptoms were characterized using the Boston Carpal Tunnel Questionnaire and Katz hand diagram in twenty-two participants (11 with symptoms, 11 with no symptoms). Using ultrasound, the thickness of the subsynovial connective tissue was measured using a thickness ratio (subsynovial thickness/tendon thickness) and gliding function was assessed using a shear strain index ((Displacementtendon − Displacementsubsynovial) / Displacementtendonx 100). For gliding function, participants performed 10 repeated flexion–extension cycles of the middle finger at a rate of one cycle per second. Findings Participants with symptoms had a 38.5% greater thickness ratio and 39.2% greater shear strain index compared to participants without symptoms (p < 0.05). Interpretation Ultrasound detected differences the SSCT in symptomatic group that was characterized by low self-reported symptom severity scores. This study found ultrasound useful for measuring structural and functional changes in the SSCT that could provide insight in the early pathophysiology associated with carpal tunnel syndrome symptoms.